Ocular Dominance Plasticity: A Mini-Review - Min SH (Eye and Brain)
Seung Hyun Min Department of Psychology, Zhejiang Sci-Tech University, Hangzhou, People’s Republic of ChinaCorrespondence: Seung Hyun Min, Email sammin95@gmail.comAbstract: Ocular dominance plasticity, the ability of the brain to change sensory eye balance, has traditionally been believed to be extremely limited in adult visual cortex. However, recent studies on short-term monocular deprivation (MD) demonstrate that its presence is prevalent in adult humans, as short-term MD is capable of significantly shifting ocular dominance in favor of the previously deprived eye. Thus, findings over the last 15 years highlight that short-term MD can be a promising alternative treatment for amblyopia, a neurodevelopmental disorder characterized by binocular imbalance. Conventionally, amblyopia has been treated with patching therapy, which shows limited effectiveness in restoring binocularity of adults and is associated with poor compliance rate and high psychosocial distress. Thus, it is an opportune time to explore how short-term MD can be utilized as an alternative treatment option for restoring amblyopic vision, especially individuals who do not respond robustly to standard treatment. This review provides an overview of foundational studies on ocular dominance plasticity in both visually intact and impaired observers. It also evaluates the potential of short-term MD as a treatment for amblyopia and suggests its future research directions, including the integration of multimodal therapeutic strategies that include short-term MD.Keywords: ocular dominance plasticity, binocular vision, amblyopia